Nitidotellina hachiensis n. sp. (Bivalvia: Tellinidae) from the Seto Inland Sea, between Honshū and Shikoku, western Japan. (3rd April 2022) - Fukuda, Hiroshi; Ishikawa, Hiroshi; Ito, Soma; Haga, Takuma
ABSTRACT: A new species of tellinid, Nitidotellina hachiensis, is described from Japan. The shell of this species is characterised by a pair of strong keels that run from the beaks to the posterior end and forms a prominent posterior notch. The recent individuals are found only in the Seto Inland Sea (Okayama, Hiroshima, Yamaguchi and Ehime prefectures), while the one fossil record so far known is from the Chibanian (middle Pleistocene) Toyohashi Formation in Aichi Prefecture, central Honshū. Living individuals are uncommon and mainly found living in sandy mud bottoms from the low tide line down to the subtidal zone in the inner parts of large bays. It can be regarded as endangered due to the recent habitat loss and water pollution of inner bay environments.